2017
DOI: 10.3389/fimmu.2017.01181
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Malignant Brain Tumors with Antibodies

Abstract: Antibodies have been shown to be a potent therapeutic tool. However, their use for targeting brain diseases, including neurodegenerative diseases and brain cancers, has been limited, particularly because the blood–brain barrier (BBB) makes brain tissue hard to access by conventional antibody-targeting strategies. In this review, we summarize new antibody therapeutic approaches to target brain tumors, especially malignant gliomas, as well as their potential drawbacks. Many different brain delivery platforms for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(46 citation statements)
references
References 148 publications
0
46
0
Order By: Relevance
“…Glioblastoma multiforme (GBM) remains an incurable malignancy, with a median survival of ∼14 months from initial presentation (1). There are several issues with developing new effective GBM therapeutics; e.g., the blood brain barrier often prevents the full therapeutic dose of many drugs reaching a brain-localized tumor; the brain is also an immunologically privileged environment that results both in a lack of checkpoint immunotherapy efficacy but also in an environment that contains activated brain associated macrophages, the microglia, which promote the growth, invasion, and survival of GBM cells (2)(3)(4)(5)(6). In the specific instance of brain tumors, whether metastatic disease or GBMs, activated microglia have a symbiotic relationship with tumor cells, each producing growth factors and cytokines that reinforces the malignant phenotype of the tumor cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastoma multiforme (GBM) remains an incurable malignancy, with a median survival of ∼14 months from initial presentation (1). There are several issues with developing new effective GBM therapeutics; e.g., the blood brain barrier often prevents the full therapeutic dose of many drugs reaching a brain-localized tumor; the brain is also an immunologically privileged environment that results both in a lack of checkpoint immunotherapy efficacy but also in an environment that contains activated brain associated macrophages, the microglia, which promote the growth, invasion, and survival of GBM cells (2)(3)(4)(5)(6). In the specific instance of brain tumors, whether metastatic disease or GBMs, activated microglia have a symbiotic relationship with tumor cells, each producing growth factors and cytokines that reinforces the malignant phenotype of the tumor cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…At this regard, it would be intriguing to assess whether the conjugation of the PDGFRβ aptamer with a fragment smaller than the entire antibody, such as a Fab lacking the Fc region, preserves the aptamer's ability to deliver the antibody cargo through the BBB. In such a case the construct could exert therapeutic bene t on brain tumors or brain metastases of breast cancer, while avoiding the side effects previously seen with antibodies entering the brain [79], thanks to the lower dose of the antibody dispensed in a conjugated form.…”
Section: Discussionmentioning
confidence: 99%
“…Smaller peptides less than 50 residues (which can cross cell membranes) have been shown to circumvent the bloodbrain barrier via receptor-mediated transcytosis. 150 Antihuman epidermal growth factor (HER2) antibodies conjugated with cell-penetrating peptides were able to cross the blood-brain barrier and prolong overall survival in BT-474 mice with brain tumors. 151 It has also been demonstrated that CAR T cells can bypass the blood-brain barrier, particularly when conjugated to cell-penetrating peptides less than 40 residues that can undergo transcytosis.…”
Section: -Neurotoxicitymentioning
confidence: 99%